Sharon E.J. Gerstel, Rural Lives and Landscapes in Late Byzantium: Art, Archaeology, and Ethnography. - Tzortzopoulou-Gregory, Lita (Journal of Greek Archaeology, 2022)
Sharon E.J. Gerstel, Rural Lives and Landscapes in Late Byzantium: Art, Archaeology, and Ethnography. pp.xvi, 207, 124 ills, 3 maps. Cambridge: Cambridge University Press, 2015. ISBN 978-0-5218-5-1596, hardcover £95.